EXTENDING JUST WAR THEORY: THE JUS AD BELLUM AND THE CAPABILITIES APPROACH TO ARMED CONFLICT - Baker, Deane-Peter; Roberts, Deborah (Scientia Militaria - South African Journal of Military Studies, 2011)
As the nature of armed conflict continues to change, so the living ethical tradition that is just war theory has to adapt to meet new challenges. This paper offers a proposal for extending just war theory by incorporating into its framework a human capabilities-based ethic drawn from the work of Martha Nussbaum. This new approach is analysed in the light of two important recent challenges to just war theory: David Rodin’s critique of the principle of national defence, and the emerging doctrine of humanitarian intervention. While the results of this analysis can only be considered to be preliminary, the authors argue that indications are that supplementing just war theory with Nussbaum’s human capabilities-based ethic, or something similar, could yield significant benefits for the ethical analysis of contemporary armed conflicts.